The two-phase gas outflow in the Circinus Galaxy. Issue Volume 15:Issue S359(2020) (March 2019) - Fonseca-Faria, M. A.; Rodríguez-Ardila, A.
Abstract: We employ Multi Unit Spectroscopic Explorer (MUSE) data to study the ionized and very ionized gas phase of the feedback in Circinus, the closest Seyfert 2 galaxy. The analysis of the nebular emission allowed us to detect a remarkable high-ionization gas outflow, out of the galaxy plane, traced by the coronal lines [Fe viii] 6089Å and [Fe x] 6374Å, extending up to 700 parsecs north-west from the nucleus. The gas kinematics reveal expanding gas shells with velocities of a few hundred km s -1, spatially coincident with prominent hard X-ray emission detected by Chandra . Density and temperature sensitive line ratios show that the extended high-ionization gas is characterized by a temperature of up to 18000 K and a gas density of n e > 10 2 cm −3 . We propose two scenarios consistent with the observations to explain the high-ionization component of the outflow: an active galactic nuclei (AGN) ejection that took place ⁓10 5 yr ago or local gas excitation by shocks produced by the passage of a radio jet.